FEATURES OF ENDOCERVICAL ADENOCARCINOMA IN RELATION TO SQUAMOUS INTRAEPITHELIAL LESIONS AND SQUAMOUS CELL CARCINOMA OF THE UTERINE CERVIX - Zivadinovic, Aleksandar; Petric, Aleksandra; Zivadinovic, Biljana; Krtinić, Dane; Zivadinovic, Jelena; Zivadinovic, Radomir (Acta medicae Medianae, 2022)
Cervical adenocarcinoma poses a huge diagnostic and therapeutic problem due to its endocervical localization and specific etiopathogenesis. Aims of the paper were: to establish characteristics of cervical adenocarcinoma in comparison to squamous cell type, to assess the validity of current diagnostic methods in cervical adenocarcinoma diagnostics, and to determine the best combination of diagnostic procedures that reduce the percentage of false negative results and demonstrate high sensitivity in cervical adenocarcinoma diagnostics. This was a prospective study comprising 180 patients operated for high-grade cervical intraepithelial neoplasia II and III, adenocarcinoma in situ and cervical carcinoma at the Clinic of Gyneacology and Obstetrics, University Clinical Center Niš. The objective of our study was especially focused on patients with a histological diagnosis of adenocarcinoma. All the patients filled out a questionnaire prior to surgery and samples for human papilloma virus (HPV) testing were collected from all of them. HPV typing was performed at the Public Health Institute Niš, by using PCR method for detecting oncogenic HPV types and genotypes. HPV result was statistically significantly more commonly associated with adenocarcinoma. NILM finding was statistically significantly more commonly associated with AC pathohistological finding, while other cytological findings were statistically significantly more commonly associated with other PH results. Normal colposcopic finding was more commonly associated with AC pathohistological finding. Irregular bleeding finding in relation to defined groups of pathological finding is statistically significant and demonstrates medium strength of association. Irregular bleedings are statistically significantly more common in adenocarcinoma in comparison to severe forms of squamous changes.